2020
DOI: 10.3343/alm.2020.40.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the QXDx BCR-ABL %IS Droplet Digital PCR Assay

Abstract: Accurate detection of BCR-ABL fusion transcripts at and below molecular response (MR) 4 (0.01% International Scale [IS]) is required for disease monitoring in patients with chronic myeloid leukemia (CML). We evaluated the analytical performance of the QXDx BCR-ABL %IS (Bio-Rad, Hercules, CA, USA) droplet digital PCR (ddPCR) assay, which is the first commercially available ddPCR-based in vitro diagnostics product. In precision analysis, the %CV was 9.3% and 3.0%, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…It should be noted that ddPCR is already being used to detect pathogens, viruses, copy number variations, and rare mutations 25 . Furthermore, the Food and Drug Administration (FDA) has recently approved the use of ddPCR for monitoring the response of chronic myeloid leukemia (CML) patients to tyrosine kinase inhibitor treatment 26 . In future studies, it will be critical to test whether the RNA mutation-based A3A assay is sensitive enough to detect A3A activity in different types of tumor samples from cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that ddPCR is already being used to detect pathogens, viruses, copy number variations, and rare mutations 25 . Furthermore, the Food and Drug Administration (FDA) has recently approved the use of ddPCR for monitoring the response of chronic myeloid leukemia (CML) patients to tyrosine kinase inhibitor treatment 26 . In future studies, it will be critical to test whether the RNA mutation-based A3A assay is sensitive enough to detect A3A activity in different types of tumor samples from cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…79 However, digital PCR may become an important complement to qRT-PCR in decisions for attempting TFR, in particular, using a ddPCR method that reports BCR-ABL1 values on the IS. 86 Factors other than the depth of BCR-ABL1 response at the time of stopping TKI may influence sustained TFR. The duration of DMR before stopping treatment and longer duration of therapy were factors in the EURO-SKI study, which is the largest discontinuation trial.…”
Section: Does Real-time Quantitative Polymerase Chain Reaction Analysmentioning
confidence: 99%
“…In addition, no outliers and no false-positive results were observed using QXDx BCR-ABL %IS ddPCR assay. They then suggested that this ddPCR kit could be a reliable and promising tool for MRD monitoring in CML patients [49].…”
Section: Dpcr To Monitor Bcr-abl1mentioning
confidence: 99%